(untitled) (Economics and region, 2017)
UDC 711.455 JEL О12, Р46 Yurii Pohorelov, D.Sc. (Economics), associate professor, head of the Department of Accounting and Audit. Poltava National Technical Yuri Kondratyuk University. Anastasiia Bilousova, Ph.D. (Economics), associate professor at the Department of Tourism and Administration. Poltava National Technical Yuri Kondratyuk University. Development of enterprises of sanatorium-resort complex in Ukraine: features of the process. It is considered in the article that development of enterprises of local sanatorium-resort complex proceeds for now slowly, mostly with evolutionary way of development. Such situation is because of trying to develop these enterprises without using concepts of built theoretical and explanatory basis of enterprise development. Development of enterprises of sanatorium-resort complex is considered in two aspects: process and result. It is shown how criteria of balance of changes in activity of enterprises of sanatorium-resort complex are implemented (reason-consequence, resource, content and chronological balance criteria). It is shown that implementing such criteria allows obtaining expected result of development. Content of stages of chronological sequence of process of developing enterprise of sanatorium-resort complex is analyzed. Keywords: enterprise, development, sanatorium-resort complex, change, process, result, aspect, criterion, chronology.